Distribution of areas of radiation generation at different frequencies in pulsar magnetospheres - Malov, I.F.; Nikitina, E.B. (Advances in Astronomy and Space Physics, 2012)
We analyse homogeneous samples of pulsars at 10 cm and 20 cm and propose to use n, the ratio of the half-width of the radiation cone θ to the minimum angular sight distance from the centre of this cone, to determine the levels of radiation generation at different frequencies in pulsar magnetospheres.